The evidence for a microRNA product of human DROSHA gene. Issue 11 (2nd November 2017) - Mechtler, Peter; Johnson, Sydney; Slabodkin, Hannah; Cohanim, Amir B.; Brodsky, Leonid; Kandel, Eugene S.
ABSTRACT: MicroRNAs are short RNA molecules that regulate function and stability of a large subset of eukaryotic mRNAs. In the main pathway of microRNA biogenesis, a short "hairpin" is excised from a primary transcript by ribonuclease DROSHA, followed by additional nucleolytic processing by DICER and inclusion of the mature microRNA into the RNA-induced silencing complex. We report that a microRNA-like molecule is encoded by human DROSHA gene within a predicted stem-loop element of the respective transcript. This putative mature microRNA is complementary to DROSHA transcript variant 1 and can attenuate expression of the corresponding protein. The findings suggest a possibility for a negative feedback loop, wherein DROSHA processes its own transcript and produces an inhibitor of its own biosynthesis.